Interactional practices in technology-rich L2 environments in and beyond the physical borders of the classroom. Issue 2 (3rd April 2022) - Jakonen, Teppo; Dooly, Melinda; Balaman, Ufuk
ABSTRACT: The current special issue is dedicated to studies exploring social interaction in second language educational environments that feature technology. In this introduction article, we contextualize the empirical studies included here with respect to the changing role of technology in education and situate them in the research tradition of multimodal and ethnomethodological Conversation Analysis (CA). We also present the individual contributions and briefly discuss how they promote a conceptualization of classrooms as pedagogically meaningful material-technological ecologies for teaching and learning actions rather than a physically delimited space.